KEANEKARAGAMAN FOSIL KAYU DI BAGIAN BARAT PULAU JAWA - Y I Mandang; D Martono (Pusat Penelitian dan Pengembangan Hasil Hutan, 1996)
A preliminai y survey on wood fossil was carried out at three fossil yards around Ciampea, Leuwiliang and Jasinga, West Java. The purpose of the survey was to find out the diversity of ancient trees of the respective areas. Fossils examined were limited to those having diameter 30 cm up only. Identification was made by examining anatomical features which can be detected by the aid of a 10 x illuminated magnifier. The results are as follows : 81. 4 percent out of 199 fossils examined are belongs to Dipterocarpaceae; among those dipterocarp fossils, 19.4 percent are Dryobalanoxylon, a genus which no longer has extant living in the present day natural forest of Java; non dipterocarp fossils are less than those of dipterocarp; among them are Alstonioxylon, Calophylloxylon, Dillenioxylon, Ochanostachysoxylon, Tenninalioxylon, and some fossil of Leguminosae. These results indicate that some time in the past, during some already gone epoch, the diversity of trees in the west region of Java island was similar to the diversity of trees in Sumatera and Kalimantan islands nowadays where dipterocarp trees are relatively abundant. Further study on the precisely described origin and accurately dated fossils is highly recommended.Key words : Dipterocarpaceae, wood fossil, Java